2013
DOI: 10.1161/circulationaha.113.002690
|View full text |Cite
|
Sign up to set email alerts
|

Stratified Meta-Analysis of Intermittent Pneumatic Compression of the Lower Limbs to Prevent Venous Thromboembolism in Hospitalized Patients

Abstract: Background-Optimal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(138 citation statements)
references
References 71 publications
(14 reference statements)
2
128
0
8
Order By: Relevance
“…13 Another, more recently published, systematic review identified 40 RCTs comparing IPC with No IPC. 19 These trials included a total of 7252 patients, were of very variable quality and included mostly surgical patients. IPC was more effective than no-IPC prophylaxis in reducing DVT [7.3% vs. 16.7%; absolute risk reduction (ARR) 9.4%, 95% CI 7.9% to 10.9%; relative risk 0.43, 95% CI 0.36 to 0.52; p < 0.01; I 2 = 34%] and PE (1.2% vs. 2.8%; ARR 1.6%; 95% CI 0.9% to 2.3%; relative risk 0.48; 95% CI 0.33 to 0.69; p < 0.01; I 2 = 0%).…”
Section: Intermittent Pneumatic Compressionmentioning
confidence: 99%
“…13 Another, more recently published, systematic review identified 40 RCTs comparing IPC with No IPC. 19 These trials included a total of 7252 patients, were of very variable quality and included mostly surgical patients. IPC was more effective than no-IPC prophylaxis in reducing DVT [7.3% vs. 16.7%; absolute risk reduction (ARR) 9.4%, 95% CI 7.9% to 10.9%; relative risk 0.43, 95% CI 0.36 to 0.52; p < 0.01; I 2 = 34%] and PE (1.2% vs. 2.8%; ARR 1.6%; 95% CI 0.9% to 2.3%; relative risk 0.48; 95% CI 0.33 to 0.69; p < 0.01; I 2 = 0%).…”
Section: Intermittent Pneumatic Compressionmentioning
confidence: 99%
“…anticoagulant thromboprophylaxis (Kakkos, 2008;CLOTS, 2013;Ho, 2013). However, compared with anticoagulant methods of thromboprophylaxis, there are relatively few high-quality studies of PCDs and no prospective randomized trials of their use as single-modality thromboprophylaxis in SCI.…”
Section: Venous Thromboembolism In Spinal Cord Injury: Risks and Riskmentioning
confidence: 99%
“…Therefore, PCDs and possibly GCSs are appropriate early after SCI, particularly if there is concomitant intracranial, perispinal, or solid organ bleeding. Combining mechanical and anticoagulant thromboprophylaxis may lead to greater protection against VTE; however, this has not been established in SCI (Kakkos, 2008;Ho, 2013). There is limited evidence that the use of PCDs or GCSs reduce the risk of VTE in patients with SCI (Geerts, 2008;Dhall, 2013).…”
Section: Rationale For Thromboprophylaxismentioning
confidence: 99%
“…Mechanical methods of prophylaxis (GCSs, IPCDs, and venous foot pumps [VFPs]) reduce the risk of VTE. [22][23][24][25][26][27][28][29][30][31][32] Mechanical prophylaxis methods are a desirable option because they do not pose bleeding concerns. 6 A meta-analysis was done to evaluate the effectiveness of GCSs for prevention of DVT in hospitalized medicalsurgical patients, and the researchers concluded that GCSs decreased the incidence of DVT, particularly in general and orthopedic surgery patients.…”
Section: Supporting Evidencementioning
confidence: 99%
“…34 Results of another meta-analysis done to examine VTE prevention in hospitalized patients also indicated that pharmacological prophylaxis combined with IPC was more effective than IPC alone. 25 Results of recent RCTs in critically ill patients also suggest that combination therapy is superior to either pharmacological or mechanical prophylaxis alone. 24,29 Interprofessional Assessment 1.…”
Section: Supporting Evidencementioning
confidence: 99%